A CLINICAL STUDY ON THE MANAGEMENT OF SANDHIVATA (OSTEOARTHRITIS) WITH A POLYHERBAL OIL FORMULATION (AYUSHI OIL) - Nayak Saurabha; Mishra Pankaj Kumar; Nayak Shobha; Gupta Ankit (International Journal of Applied Ayurved Research, 2016)
Sandhivata is a painful condition of joints due to vitiation of Vata and it is one among eighty types of Vata disorder described by acharya Charaka, which affects mostly the movable joints of elderly people,characterized by shotha (swelling) and shula (pain). It can be correlated with osteoarthritis with regard to sign and symptoms. Ayurvedic acharyas described snehana and swedana as main line of treatment in the management of Sandhivata. Keeping that in view a clinical trial was conducted in 100 patients of Sandhivata with a polyherbal oil formulation (Ayushi oil) as bahya snehana (external oleation) followed by swedana (fomentation) for a period of 20 days.To assess the effect of therapy objectively, all the signs and symptoms of Sandhivata were given a score depending upon there severity before and after treatment.The results were analyzed statistically and found highly significant in reducing all cardinal symptoms of Sandhivata.